Harmonization of Accounting Treatment of Property, Plant, Equipment and Intangible Assets - Babinec, Matúš; Krupová, Lenka, 1964-; Mejzlík, Ladislav, 1961-; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2009)
The globalization of world economy has inevitably affected also the movements in harmonization process of accounting standards around the world. International Financial Reporting Standards have become the ultimate accounting and reporting tool of most developed countries. The only remaining counterpart -- the US GAAP, is slowly subsiding to the enormous spread momentum that IFRS gained in recent years. In this setting I examine the application of International standards on accounting treatment of Property, Plant and Equipment, and also the Intangible Assets. Subsequently I compare this treatment to US GAAP and document all major differences still persistent at the end of year 2008. Considering that there are still many divergences between the two sets of standards, I try to document their impact on the reporting and presentation of financial statements of several blue chip companies. My analysis suggests that differences in reported numbers depending on standards chosen can distort comparability of financial statements and performance assessment, thus potentially biasing the decision making process of involved stakeholders.
Vedoucí práce: Lenka Krupová
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Způsob přístupu: Internet
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2009
Rok obhajoby 2009
Keywords: účetnictví a finanční řízení podniku [obor dipl. práce]; diplomové práce; master's theses